STEREOTYPE OF BLACK FEMALE CHARACTERS IN TONI MORRISON’S THE BLUEST EYE - Mayasakti, Novia Caessar; Asanti, Chris; Fatimah, Fatimah (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
Stereotype is one of the issues which happens in America’s multicultural society up to now. This research investigates two objects. First, the type of stereotype: Black female stereotype and the second is stereotype formation which applied in Toni Morrison’s The Bluest Eye. Qualitative method was used in this research. The theories used to approach this research are taken from Mahassen Mgadmi (2009) and James L. Hilton and William von Hippel (1996). The research revealed that there are two main findings in this research. First, the type of stereotype found in the novel is Black female stereotype which represented by two characters. Second, there are two stages of stereotype formation occurred in the novel: Illusory Correlation and Self-Fulfilling Prophecy. The acts of Self-fulfilling Prophecy are harsh word choice, verbal tones, degree of interpersonal distance, facial expressions, and teaching methods or classroom practices. Hence, it can be assumed that the black female characters in the novel are still defined by their physical appearances which then strengthen the stereotype towards them. In addition, the stereotype that happens is actually formed in their mind, and then it is shown in their actual behaviors.